2012
DOI: 10.1063/1.3684633
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous solutions of divalent chlorides: Ions hydration shell and water structure

Abstract: By combining neutron diffraction and Monte Carlo simulations, we have determined the microscopic structure of the hydration ions shell in aqueous solutions of MgCl(2) and CaCl(2), along with the radial distribution functions of the solvent. In particular the hydration shell of the cations, show cation specific symmetry, due to the strong and directional interaction of ions and water oxygens. The ions and their hydration shells likely form molecular moieties and bring clear signatures in the water-water radial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
71
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 32 publications
16
71
0
Order By: Relevance
“…In terms of corrosive aqueous environments, the presence of halide anions can profoundly alter the structure and dynamics of interfacial water layers [18,33]. While the solvation characteristics of interfacial layers are expected to play an important role in corrosion initiation, they have received much less attention to date [7,33]. Recently, we have shown that ionic solvation of water near passive oxides could also play an important role in influencing halide ion adsorption and transport [18].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In terms of corrosive aqueous environments, the presence of halide anions can profoundly alter the structure and dynamics of interfacial water layers [18,33]. While the solvation characteristics of interfacial layers are expected to play an important role in corrosion initiation, they have received much less attention to date [7,33]. Recently, we have shown that ionic solvation of water near passive oxides could also play an important role in influencing halide ion adsorption and transport [18].…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, there are several important questions pertaining to solvation dynamics near electrochemical interfaces, ionic transport across electrochemical double layers as well as interfacial molecular order in a typical electrochemical environment that are not yet well understood [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…37 position of the first maximum (r max ) and minimum (r min ) of the Cl−O and Cl−D pair correlation functions and the corresponding coordination numbers are reported in Table I, together with experimental values. The latter ones differ depending on the technique used (i.e., neutron diffraction or X-ray measurements) and the type of counterions present in the solution, 5,6,[36][37][38][39][40][41] whose effect however appears to be minor. The dependence of experimental data on concentration is instead more pronounced (at least for the Cl−D coordination).…”
mentioning
confidence: 99%
“…Details about the sample preparation and data analysis can be found in refs. [16][17][18] and [12,19,20] for salt solutions and confined water, respectively. The BBD spectroscopy experiments have been performed at our home laboratories, by using different confining media for water, namely a powder of lysozyme protein at hydration h= 0.30 g/g (grams of water per gram of dry material) and two silica substrates (xerogel and MCM41) at hydration h = 0.57 g/g and 0.43 g/g, respectively.…”
Section: Methodsmentioning
confidence: 99%